Influence of land type and cropping on the distribution of micronutrients in Ganges river floodplain soils of Bangladesh (Dhaka University Journal of Biological Sciences, 2023)
The soils of Ganges River Floodplain (GRFP), an important crop growing zone of the country, are known to be widely deficient in micronutrients. The study was conducted to relate the distribution and the fate of soil micronutrients in relation to land type, soil properties and cropping practices in GRFP.A total of 52 locations were selected for sample collection from across GRFP, varied in land type, soil series and cropping pattern, and analysed for DTPA extractable iron (Fe), manganese (Mn), copper (Cu), zinc (Zn) and hot water soluble boron (B). Most of the samples were found deficient in Zn and B, while a moderate number of samples were Fedeficient. The major reason of micronutrient deficiency was found to be high soil pH. Among the four soil series studied, Ghior series was most deficient in Zn and B, implying pedogenic differences among the soils. Significant effect of contrasting land types on the distribution of soil micronutrients was observed although the effect was not consistent. The rice-rice cropping pattern was found to have slightly higher contents of Mn, Zn and B compared to rice-non-rice pattern which might be due to longer submergence period in the soils under rice-rice pattern.Dhaka Univ. J. Biol. Sci. 32(1): 91-105, 2023 (January)